Clinical impact of optical coherence tomography findings on culprit plaque in acute coronary syndrome: The OCT‐FORMIDABLE study registry. Issue 7 (10th May 2018) - Iannaccone, Mario; Souteyrand, Geraud; Niccoli, Giampaolo; Mancone, Massimo; Sardella, Gennaro; Tamburino, Corrado; Templin, Christian; Gili, Sebastiano; Boccuzzi, Giacomo G; D'Ascenzo, Fabrizio
Abstract: Background: Aim of this study was to evaluate the clinical impact of the culprit plaque features assessed by optical coherence tomography (OCT) in patients with acute coronary syndrome (ACS). Methods: The OCT‐FORMIDABLE register enrolled retrospectively all consecutive patients who perform OCT on culprit plaque in patients with ACS in nine European centres. The primary endpoint was the prevalence of culprit plaque rupture (CPR) in patients experiencing major adverse cardiovascular events (MACEs). Secondary endpoint was the prevalence necrotic core with macrophage infiltrations (NCMI) in the patients experiencing MACEs. Results: Two‐hundred and nine patients were included in the study. Mean age was 60.1 ± 12.9 years old, 19.1% were females. Main clinical presentation was ST‐elevation myocardial infarction (55%). At OCT analysis, CPR was observed in 71.8% patients, while 31.6% presented NCMI. During follow‐up (12.6 ± 14.5 months), 11% of the patients experienced MACEs. The presence of CPR (HR 3.7, 1.4‐9.8, P  < .01) and NCMI (HR 3.3, 1.6‐6.6, P  < .01) were independent predictors for MACEs, while dual antiplatelet therapy with prasugrel/ticagrelor at discharge (HR 0.2, 0.1‐0.6, P  < .01) were protective. The protective impact of new antiplatelet drugs was reported only in patients with CPR while in patients without any of the baseline clinical or procedural features impacted on MACEs. Conclusions: CPR and the presence of NCMI are independent predictors of worse outcome. Patients with CPR seem to benefit more of an intensive therapy, both from a pharmacological and interventional point of view. (NCT02486861)